Policy Transformation on the Implementation of Public Services in Sub- districts - Firdaus; Ahmad Fitra Yuza (International Conference On Law And Social Sciences, 2024)
Sub-districts are an important key to community services at the regional level. The problem of public services in Indonesia occurred in several periods of government administration starting during the new order period until the reformation. The new order reflected the greatest power in the hands of the state, including in the affairs of public services so that socio-political forces and small market forces had a significant influence on public policy, even in its implementation. While the reform era, public services are reviewed in accordance with the context by utilizing decentralization through the authority given by the central government to local governments so that they must be able to provide an increase in the quality of good public services. Policy transformation characterized by changes in regulations from time to time is quite significant. The sub-district, which is one of the frontlines in the delivery of public services aimed at cutting the bureaucracy, still has weaknesses where the delegation of government duties to the limited sub-district head makes the quality of public services not maximized, making them hesitant to innovate to support basic services. Meanwhile, transformation is needed to overcome modern challenges by utilizing innovation and adaptation that can create efficiency and good public services. Nevertheless, the achievement of the main objectives of bureaucratic reform is carried out as a form of public service transformation in the sub-district is also carried out through electronic- based public services (e-service), strengthening community supervision of public service performance, strengthening the innovation ecosystem, and strengthening integrated services.